Exploring teachers’ corrective feedback strategies in English for specific purposes (ESP) descriptive text writing - Alfayed, Affied; Hartiningsih, Sri; Hamdani, Muhammad Fadhil (Journal of Language and Pragmatics Studies, 2025)
The growing demand for vocational education in Indonesia is driven by an increasingly competitive job market, requiring students to develop specialized skills, including proficiency in English for Specific Purposes (ESP). English teachers play a crucial role in enhancing students’ writing abilities, particularly in crafting descriptive texts relevant to their fields of study. However, limited research has explored how teachers provide corrective feedback in ESP writing instruction. This study investigates the corrective feedback strategies employed by an English teacher in a vocational school when teaching descriptive text writing. It also examines the rationale behind the teacher’s feedback practices. A qualitative case study approach was used, with data collected through interviews, classroom observations, and an analysis of students' written assignments. The findings indicate that the teacher primarily utilized oral corrective feedback during writing instruction, focusing on product description texts. The feedback strategies included explicit correction, metalinguistic feedback, and recasts. Explicit correction involved directly pointing out errors and providing correct alternatives, while metalinguistic feedback prompted students to self-correct by offering linguistic explanations. Recasts, on the other hand, involved reformulating students' erroneous statements in a more accurate form. The study further revealed that the teacher’s feedback approach was influenced by personal teaching experience and beliefs about effective language instruction. These findings highlight the importance of oral corrective feedback in improving students’ writing skills in ESP contexts. They suggest that teachers should adopt varied feedback strategies tailored to students’ needs to enhance learning outcomes. Future research could explore the long-term effects of different corrective feedback methods on students' writing development in vocational education settings.